Substituent effect on iron phthalocyanines as cyclohexene oxidation catalysts - (:unkn) unknown (World Scientific, 2021)
Two iron phthalocyanines peripherally octasubstituted either with electron-withdrawing isobutylsulfonyl moities or electron-donating isobutoxy moieties were designed to investigate the effect of the substitution pattern on their oxidation catalytic activity, and were then tested in oxidation of cyclohexene as a reaction model. For both catalysts, the main product of oxidation was 2-cyclohexen-1-ol which is an allylic oxidation product. The electron-withdrawing isobutylsulfonyl substituted iron phthalocyanine 1exhibited better catalytic activities than the electron-donating isobutoxy substituted iron phthalocyanine 2. © 2021 World Scientific Publishing Company.
Keywords: cyclohexene; iron; olefin; oxidation catalyst; Phthalocyanine